Pengaruh Harga dan Kualitas Produk Bawang Merah (Allium Ascalonicum L.) Terhadap Keputusan Konsumen untuk Berbelanja pada Kebun Praktek Fakultas Pertanian Universitas Nusa Nipa Indonesia - Maria Anastasia Sabu Belo; Gabriel Otan Apelabi; Fiator Nong (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study was to determine the influence of price and product quality on purchasing decisions on Organic Shallots. Data obtained from distributing questionnaires to 30 respondents as a sample using a Likert scale. The data were processed and analyzed using multiple linear regression. The R2 test result is 0.602 or 60.2%, meaning that the purchasing decision variable is explained by the trust and quality variable by 60.2%. The results of the F test show that f count 20.458,> f table 2.52, thus simultaneously the price and product quality variables have a positive and significant effect on purchasing decisions on buyers of Organic shallots. While the t test results showed a significant effect of price on purchasing decisions as evidenced by t count 2.347> t table 1.690, a significant effect of cusality on purchasing decisions on buyers of organic shallots as evidenced by t count 6.004> t table 1.690. Then the regression equation obtained Y = 196.979 + 2.658 + 6.004. This means that the constant value is 196.979, this indicates that if the price and quality of the product are ignored, the purchase decision for the buyer of shallots is 196.979. The regression coefficient of the price variable is -2.658, meaning that every 1 unit price increase, an increase in purchasing decisions for organic shallot buyers will be followed by -2.658. The regression coefficient for the product quality variable is 0.422, meaning that for every 1 unit quality increase, an increase in purchasing decisions for organic shallot buyers will be followed by 6.004. The results of this study are that the price and product quality have a significant effect on purchasing decisions on organic shallot buyers in the practical gardens of the Faculty of Agriculture, Nusa Nipa University of Indonesia, Sikka Regency.